Breast Reconstruction With Autologous Fat Graft Mixed With Platelet-Rich Plasma. (August 2013) - Gentile, Pietro; Di Pasquali, Camilla; Bocchini, Ilaria; Floris, Micol; Eleonora, Tati; Fiaschetti, Valeria; Floris, Roberto; Cervelli, Valerio
Background . The purpose of this study was to review the authors' experience of fat grafting, evaluating the effects related to the use of fat grafting with platelet-rich plasma (PRP) in the improvement of fat volume in breast reconstruction and comparing the results with a control group (only centrifuged fat grafting). Methods . A total of 50 patients aged between 19 and 60 years affected by breast soft-tissue defects were analyzed at the Plastic and Reconstructive Department of the University of Tor Vergata. They were treated with fat grafting + PRP. The control group (50 patients with breast soft-tissue defects) were treated with centrifuged fat grafting injection according to Coleman's procedure. Results . The patients treated with PRP added to the autologous fat grafts showed a 69% maintenance of the contour restoring and of 3-dimensional volume after 1 year, whereas the patients of the control group treated with centrifuged fat grafting showed a 39% maintenance. Conclusion . PRP mixed with fat grafting leads to an improvement in maintaining breast volume in patients affected by breast soft-tissue defects.